Recurrent nocturnal hypoglycaemia as a cause of morning fatigue in treated Addison's disease – favourable response to dietary management: a case report. Issue 1 (December 2015) - Petersen, Kristina; Rushworth, R.; Clifton, Peter; Torpy, David
Abstract Background Addison's disease, or primary adrenal insufficiency, is often associated with reduced well-being and fatigue despite use of currently recommended adrenal hormone replacement. Hypoglycaemia is a known manifestation of glucocorticoid deficiency, but is generally considered rare in adults and not relevant to troubling ongoing symptoms in patients with Addison's disease. Case presentation A 43 year old woman with a three year history of Addison's disease complained of severe morning fatigue and headaches, despite standard glucocorticoid replacement therapy in the form of thrice daily hydrocortisone and mineralocorticoid replacement with fludrocortisone. Alternative glucocorticoid replacement regimens and the addition of dehydroepiandrosterone replacement therapy had no effect. Nocturnal hypoglycaemia was suspected and a 4-day continuous glucose monitor system (CGMS) revealed hypoglycaemia (interstitial glucose < 2.2 mmol/L) between 0200–0400 h on 3 of 4 days. The patient was counselled to take an evening snack designed to ensure slow absorption of ingested carbohydrates. Nocturnal hypoglycaemia was then absent on follow up CGMS assessment. The patient noted a marked symptomatic improvement in morning symptoms, but with persistent fatigue during the day. Conclusion Currently, the best strategy for control of non-specific symptoms in treated Addison's disease is unknown, but it may be that investigation for hypoglycaemia and treatment, where necessary, could assist some sufferers to achieve improved wellbeing. A systematic study of this phenomenon in Addison's disease is required.